Benzophenone and xanthone derivatives from the inflorescences of Garcinia cowa - Trisuwan K. (Pharmaceutical Society of Korea, 2015)
The purification of the acetone extract from the inflorescences of Garcinia cowa led to the isolation of a new benzophenone derivative, cowanone (1), together with seven known xanthones, α-mangostin (2), ?-mangostin (3), cowanin (4), fuscaxanthone A (5), 9-hydroxycalabaxanthone (6), garcinianone A (7) and cowanol (8). The structures of the isolated compounds were elucidated by analysis of their spectroscopic data including 1D and 2D NMR data. All isolated compounds were evaluated for their antibacterial activities against Staphylococcus aureus (SA) and methicillin-resistant S. aureus (MRSA).